The effect of option listing on financing decisions. (12th July 2022) - Hong, Eunpyo; Park, Min C.; King, Tao‐Hsien Dolly
Abstract: This paper investigates the effect of option listing on corporate financing decisions. Firms experience a significant drop in leverage, which is driven mainly by an increase in new equity issues. This effect is more prominent in firms with greater information asymmetry and lower percentages of quasi‐index and transient investors before listing and those with active options trading after listing. After options are listed, the newly listed firms hold more cash and engage in more acquisitions, which are funded mainly by equity issues. These findings suggest that option listing has a significant impact on financing decisions because of lower information asymmetry and that firms use the post‐listing equity to build up financial slack and support major investments, such as acquisitions.